Retrospective study of maternal near misses in a tertiary care institute - Sharma, Swati; Aherwar, Rupa; Jawadhe, Shashikala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Traditionally, the analysis of maternal deaths has been the criteria of choice for evaluating women’s health and the quality of obstetric care. The objective of the study was to determine the (Maternal near miss incidence ratio) frequency of maternal near miss and to study the demographic profile, etiology and lifesaving interventions done in near miss cases. Methods: A retrospective study was conducted in department of Obstetrics and Gynecology in Chirayu medical college, Bhopal. This is a tertiary care institution and a referral hospital. The study was done during a period of one year from August 2014 to August 2015. During this period 1500 antenatal patients were admitted; of which 30 patients with potentially life threatening conditions were diagnosed; who met WHO 2009 criteria for near miss; along with clinical/laboratory evidence for the same, were selected for the study. Results: The Maternal near miss incidence ratio was 20/1000 live births in our study. In our study 53.3% were in 21-25years age group with a mean age of the patients was 26.3 + 5 years. 93.3% were unbooked, 66.6% were primigravidas, 73.3 % were term patients, 60% were low income group, 73.3% were urban residents, and 76.7% were antenatal cases. In our study 60% patients presented with bleeding PV, 56.3% presented with PPH, 13.3% presented with ecclampsia and 26.7% had pregnancy with jaundice. All patients required ICU for monitoring and interventions as multiple blood transfusions (60%), dialysis (13.3%), liver function monitoring (26.7), encephalopathy (3.3%) and DIC monitoring (20%). 6.7 % required ventilator and 13.3% were managed for multiorgan failure in our study. 26.6 % were managed with uterine packing and MRP, 16.7% were managed with uterine balloon temponade and post-partum hysterectomy in 16.7% cases and internal iliac ligation was done in 13.2% cases in our study. Cesarean section was done in 16.7% cases, 66.6% had vaginal delivery and 16.7% underwent hysterectomy due to haemorrhage and post-partum endometritis in our study. Conclusions: The study concludes that maternal near miss could be an important tool to assess maternal morbidity burden. We can utilize our knowledge of maternal near miss cases to reduce maternal mortality by identifying preventable factors and doing vigilant timely interventions.